ANTI-BACTERIAL EFFECTS OF GLYCOSIDES EXTRACT OF GLYCYRRHIZA GLABRA L. FROM THE REGION OF DJAMÂA (SOUTH-EAST OF ALGERIA) - Soulef, Kriker; Yahia, A. (Journal of Medicinal Herbs and Ethnomedicine)
The natural extracts of plants contain a variety of biologically active molecules. In this context, we attempted to evaluate the antimicrobial activity of some extracts prepared from the root of Glycyrrhiza glabra L., which grows in the region of Djamâa (south of Algeria). The qualitative analysis of these extracts revealed the presence of plant glycosides, which is confirmed by a quantitative analysis based on the detection test of glycosides, who demonstrated that the extracts are rich in these molecules, where the content of glycoside reached (10 %) for the ethanol extraction. The evaluation of the glycoside extract antimicrobial activity revealed a strong effect of inhibition on different strain of bacteria, when it was responsible for a large zone of inhibition of the bacterial strain Pseudomonas aeruginosa, compared to Escherichia coli and staphylococcus aureus. From these results, we can say that the glycoside extracts have different antibacterial effects depending on the species.